(untitled) (Bangladesh Rice Journal, 2019)
Field trials were conducted for two years to evaluate the integrated effect of poultry manure (PM) and chemical fertilizers on yield, nutrient balance and economics of rice at BRRI, Gazipur (AEZ-28 and land type- High Land) during Boro 2009 to T. Aman 2010. Eight treatment combinations, where PM @ 1, 2, 3 t ha-1 with IPNS (Integrated plant nutrient system) based dose and PM @ 1, 2, 3 t ha-1 with 50% STB (soil test based) dose along with a control and 100% STB chemical fertilizer were tested. Immediate effects of manure and fertilizer were evaluated in Boro season and residual effects were observed in the following T. Aman season. Application of PM @ 2 t ha-1 with IPNS based chemical fertilizer or PM @ 3 t ha-1 with 50% STB dose gave higher grain yield in Boro season. Some residual effects in the succeeding T. Aman rice were observed where PM was used @ 3 t ha-1. The highest net return was obtained with 3 t PM ha-1 with 50% STB dose. A positive nutrient balance of phosphorus and sulfur were observed in PM and chemical fertilizer treated plots. Bangladesh Rice j. 2018, 22(2): 71-77